Supplementation of Multiple Enzymes and Organic Trace Mineral Supplementation to the Diets Containing Sub-Optimal Energy on Performance and Carcass Traits of Commercial Broilers - Krishna, Daida; Gurram, Srinivas (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to study the performance and carcass parameters of broilers fed with sub-optimal metabolizable energy (100 and 200 kcal/kg less ME) diets supplemented with multiple Enzyme (400g/ton feed) and organic trace mineral supplement. A total of 300-day-old commercial broiler chickens were distributed in a completely randomized design into 6 treatments with 10 replicates of 5 chicks each. Treatments comprised of T1- basal diet (BD) without enzyme (EZ) or organic mineral (OM) supplementation; T2- 100 kcal/kg less metabolizable energy (ME) without EZ and OM (BD 1); Â T3- 100 kcal/kg less ME with EN (BD1+EZ); T4- 200 kcal/kg less ME without EN and OM (BD 2); T5- 200 kcal/kg less ME with EZ (BD2+EZ); T6- BD with organomin supplementation (BD+OM).The results revealed significantly (P<0.05) improved body weight in all dietary treatments groups except BD2 (200 kcal/kg less ME without EN and OM) at 6 weeks of age. Significantly (P<0.05) higher feed intake was observed in BD1+EZ, BD+OM and BD1 compared to control and other treatment groups. No significant difference was recorded in feed efficiency among different dietary treatments. All dietary treatments failed to exert any significant (P>0.05) influence on various carcass parameters except abdominal fat which was significantly high in BD+OM group compared to other treatments.